Investigating Oral Capability and Total Immersion Program at EFL Classroom - Muhammad Hanafi; Andi Sadapotto (Celebes Journal of Language Studies, 2021)
The aims of this article is to describe that total immersion program in teaching English can improve students oral capability. This article is made from research result which used pre-test and post-test design. The population of the article is the ninth grade of SMP Negeri 3 Panca Rijang there are two classes. The writer applied random technique that took one of the two classes and sample of this article was IX.2 class with 20 students. The instrument of this article was speaking test which would be administered in pre-test and post-test. The pre-test would be used to find the prior knowledge of oral capability, while post-test would be used to find oral capability achievement after treatment is given. The result of this article showed that total immersion program was effective to improve oral capability at the ninth grade of SMP Negeri 3 Panca Rijang especially IX.2 class. It could be proved from their mean score in post-test (56.95) was higher than their mean score in pre-test (48.50), and the t-test value (10.934) was greater than t-table (a = 0.05; df= 9; t table = 2.262, this means that H1 was accepted.